Розвиток ринку консалтингових послуг: зарубіжний досвід і реалії України - Сурженко, Нонна Вікторівна; Сурженко, Нонна Викторовна; Surzhenko, Nonna (My University, 2018)
UK: Автор проаналізував динаміку розвитку зарубіжного і вітчизняного ринку консалтингових послуг, всебічно дослідив організаційно-економічні аспекти та проблеми консалтингової діяльності, визначив перспективи подальшого розвитку вітчизняного ринку консалтингових послуг. EN: In modern conditions, many countries find a solution to the problems of economic growth in improving the quality of management based on the acquisition, use and transfer of knowledge. At the same time, the skill level of the management of enterprises, organizations, and firms, in some cases, is insufficient for solving such tasks due to the lack of certain skills and knowledge. Also, their insufficient amount hinders the intro-duction of the necessary innovations.
Development of the consulting services market: foreign experience and realities of Ukraine
Keywords: консалтингова діяльність; міжнародний консалтинг; консалтингові послуги; маркетингове дослідження; структурний аналіз; консалтингові компанії; consulting activities; international consulting; consulting services; marketing research; structural analysis; consulting companies